2022
DOI: 10.1155/2022/3158956
|View full text |Cite|
|
Sign up to set email alerts
|

Clinicopathological Features of 166 Cases of Invasive Ductal Breast Carcinoma and Effect of Primary Tumor Location on Prognosis after Modified Radical Mastectomy

Abstract: Objective. To investigate the clinicopathological features of 166 cases of invasive ductal carcinoma (IDC) of the breast and to analyze the effect of the location of the primary tumor on the prognosis of modified radical mastectomy. Materials and Methods. The clinical data of 166 patients with IDC who underwent modified radical mastectomy in our hospital from May 2015 to May 2017 were retrospectively analyzed. The clinicopathological features of IDC patients were recorded. Univariate analysis and the multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In this study, to mitigate the potential confounding efects of disease subtype, treatment modality, and other complications on the study outcomes, all enrolled participants were surgically diagnosed with breast invasive ductal carcinoma (IDC) and underwent an initial modifed radical mastectomy. IDC, as a common type of breast cancer, is characterized by the continuous growth and spread of malignant cells in the breast duct and gradually invade the surrounding normal tissues [33]. Te causes of the disease are various, including the imbalance of genetic factors and abnormal breast tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, to mitigate the potential confounding efects of disease subtype, treatment modality, and other complications on the study outcomes, all enrolled participants were surgically diagnosed with breast invasive ductal carcinoma (IDC) and underwent an initial modifed radical mastectomy. IDC, as a common type of breast cancer, is characterized by the continuous growth and spread of malignant cells in the breast duct and gradually invade the surrounding normal tissues [33]. Te causes of the disease are various, including the imbalance of genetic factors and abnormal breast tissue.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, clinical practice seeks every day to promote individualized treatment; therefore, the search for potential prognostic biomarkers, target molecules, and signaling pathways that may be associated with the disease is considered an important step toward achieving. 27,28 Prognostic markers are also helpful in determining the effectiveness of the established intervention (surgical or pharmacological treatment), the probability of recurrence, and the establishment of additional follow-up and treatment strategies. 29 Due to BC's heterogeneity and high capacity for metastasis, despite efforts to identify biomarkers and the variety of genetic factors currently accepted, an increasing number of patients are demanding personalized treatments, which necessitates the development of novel biomarkers for diagnosis and prognosis that allow for an early evaluation of the development of the pathology to formulate effective diagnosis and treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%